The Importance of Managing HbA1c in Coronary Artery Disease: Keep It Low - Djanggan Sargowo (Universitas Brawijaya, 2020)
Coronary Artery Disease (CAD) is the most prevalent cardiovascular disease, which remains the leading cause of death worldwide. In Indonesia, it accounts for approximately 1.5% of the entire population. Diabetes mellitus (DM) is taken into consideration as one of the most potent risk factors for cardiovascular diseases. HaemoglobinA1c (HbA1c) reflects a long-term glycemic control and is used as a valuable diabetes biomarker. High serum glucose levels, expressed as glycated hemoglobin levels in diabetics or non-diabetics, are related to varying degrees of systemic inflammation and promote the release of the proinflammatory cytokines. The association between higher glycated serum HbA1c levels and the severity of the coronary disease is well known. The predictive value of HbA1c for CAD severity, re-hospitalization, and the mortality of cardiovascular disease had been studied extensively since 2004. Numerous previous trials discovered that severity of CAD correlated with the elevation of HbA1c levels, suggesting it as a broad surrogate marker for CAD. Thus, HbA1c is currently considered as an independent risk factor for CAD. A higher level of HbA1c and the presence of factors associated with ongoing atherosclerosis and extensive CAD are concomitantly contributing to the higher major adverse cardiovascular events (MACEs) incidence and long-term mortality.